Superficial fungal infections in the south of France—is fusariosis the next emergent onychopathy?. (9th February 2023) - Landreau, Anne; Simon, Loïc; Delaunay, Pascal; Pomares, Christelle; Hasseine, Lilia
Abstract: In France, onychomycoses represent about 30% of superficial mycoses seen by dermatologists. In recent years, an increased number of mycoses have been observed due to non-dermatophytic moulds. The purpose of this study was to evaluate the epidemiological profile of identified superficial fungal infections in the Laboratory of Parasitology–Mycology of the University Hospital of Nice over a 2-year period. A retrospective study was performed from the nail, skin, and scalp samples of patients analyzed from January 2018 to December 2019. In this study, 3074 samples (54.2% nails, 39.7% skin, and 6.1% scalp) were analyzed representing 1922 patients. Among them, 809 (42.1%) patients were sampled by dermatologists and 1113 (57.9%) were sampled by our experts in the clinical unit of the University Hospital of Nice. In total, 1159 (37.7%) samples had a positive culture (1195 strains identified) including 712 (59.6%) dermatophytes, 345 (28.9%) yeasts, and 138 (11.5%) other filamentous moulds. Trichophyton rubrum was the main dermatophyte (563; 47.1%) followed by T. interdigitale (84; 7.0%), and T. soudanense (25; 2.1%). Yeasts were mostly represented by Candida albicans (155; 13.0%). Among the other moulds, Fusarium sp. was the most isolated (61; 5.1%). Dermatophytes stay predominant in superficial fungal infections where the anthropophilic species T. rubrum was found in almost half of the positive cultures. Interestingly, moulds represented an important part of infections in our population. This study highlights the increasing share of Fusarium sp. superficial fungal infection in our patients' population, perhaps requiring a major therapeutic adaptation in the years to come. Lay Summary: We assessed the epidemiological profile of superficial fungal infections in the Laboratory of Parasitology–Mycology of the Hospital of Nice, over a 2-year period. Among our samples, dermatophytes remain predominant, mainly the species Trichophyton rubrum and we had a large proportion of Fusarium .